Assessing the quantity and quality of marine protected areas in the Mariana Islands - Mana‘oakamai Johnson, Steven; Villagomez, Angelo O. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are ubiquitous in global ocean conservation and play a pivotal role in achieving local, national, and regional area-based conservation targets. Often, such targets are merely met on “paper” and lack the political or managerial resources to produce positive conservation outcomes. Here, we apply the MPA Guide – a framework for assessing the quantity and quality of marine protected areas – to Guam and the Commonwealth of the Northern Mariana Islands (CNMI), two U.S. territories in the Western Pacific. We reviewed the enabling legislation and applicable management documents for all MPAs (n=18). We found that all but three (3) MPAs in the Mariana Islands are actively managed, and these areas are either fully or highly protected – the highest tier of the MPA Guide. Lightly protected areas are associated with high use/high-density tourism activities. Total area protected varies at the jurisdictional scale: 0.83% of Guam’s territorial waters (out to 12 nm) and 23.73% of EEZ under some spatial management; CNMI has 20.39% of territorial waters and 25.91% of EEZ in MPAs. These results emphasize the importance of quality, quantity, and scale when determining effective conservation, especially in overlapping and contested jurisdictional authority areas.